Analisis Kepatuhan Pengungkapan ESG pada Perusahaan BUMN Sektor Transportasi Tahun 2023 - Wita Yulita; Agus Munandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Transportation has a role in contributing to carbon emissions and social, especially BUMN companies where BUMN is an extension of the government in the context of services to the community so that transparency and accountability as a form of accountability for the performance of BUMN companies in the Transportation sector. The purpose of the study is to analyze the level of compliance with ESG disclosure in BUMN Transportation Sector Companies. The object of research is descriptive qualitative based on the 2023 Sustainability Report. The results of this study reveal that BUMN companies in the transportation sector (have not fully loaded environmental, social, and governance information) GRI2021 standards. This study has not analyzed ESG compliance and integration with financial performance.